Effects of fertilization on soil ecological stoichiometry and fruit quality in Karst pitaya orchard - Jiajia Chen; Weiwei Ran; Yuanqi Zhao; Zhibing Zhao; Yuehua Song (Scientific Reports, 2024)
Abstract Pitaya (Hylocereus undulatus) is a significant cash crop in the karst region of Southwest China. Ecological stoichiometry is an essential method to research biogeochemical cycles and limiting elements. The purpose of this study was to explore the stoichiometric characteristics of C, N, and P in Karst pitaya orchards and fruit quality and to elucidate the mechanism and process of nutrient cycling. The results showed that: (1) Fruit quality was highest under the combination of chemical and organic fertilizers. Compared to the control, the contents of per-fruit weight, vitamin C, and soluble sugar increased significantly by 55.5%, 60.7%, and 23.0%, respectively, while the content of titratable acidity decreased significantly by 22.0%. (2) The content of soil nutrients under fertilization stress showed a downward trend in general, as did microbial biomass and extracellular enzyme activities. (3) Different fertilization treatments significantly affected the soil-microbial stoichiometry C:N ratio, C:P ratio, with research areas being significantly limited by C and P. (4) Spearman and PLS-SEM (partial least squares-structural equation model) analysis results showed that under the influence of fertilization, there was a significant positive effect between microorganisms and soil nutrients, but a significant negative effect between soil nutrients and quality. The results of this study offer an innovative perspective on pitaya quality research in Karst areas.